Design And Build A Double Roll Type Pecan Breaking Machine With A Power Of 0.5 Hp - Marslino Simanjuntak, Arion; sahat; Naibaho, winfrontstein (International Journal of Science, Technology & Management, 2022)
Pecan is one of the spices that become an ingredient in the process of the food and cosmetic industry. The pecan separator machine is made to facilitate and speed up the process of breaking the pecan fruit in order to increase work efficiency in the hope that the machine can achieve high efficiency in the form of good fruit yields. The purpose of this pecan fruit separator machine is to help facilitate the community in processing pecan fruit to the maximum of its production, and the community can also increase the processing productivity of pecan fruit, which can improve the community's economy. The research method applied in this study is an experimental method, namely the initial stage of designing a double roll type pecan breaking machine using Auto CAD. Then build the machine in the workshop based on the design that has been done before. The stages passed are making design drawings in Auto CAD and analyzing the components used in the pecan breaking machine. Such components are the frame, inlet funnel, shaft, breaker roller, bearing and outlet funnel. From the results of the analysis, the motor power is 0.5 HP with a rotation of 1400 rpm. The belt length used from the calculation of the pulley size on the 3" machine and the pulley on the 10 breaking roll is 42". For breaking rollers the outer diameter of the roller = 120 mm, the inner diameter of the roller = 100 mm, and the length of the roller = 190 mm. The shaft on the drive motor is 24 mm in diameter. The shaft isestimated to be of S30C carbon steel with tensile strength = 48 kg/mm².